Configuração urbana e conforto térmico ao nível do pedestre: estudos na cidade de São Carlos - SP - Fernandes, Maria Eugênia (Universidade Federal de São Carlos, 2019)
Urbanization has been causing changes in the urban climate, altering the temperature and relative humidity of the air, the precipitation indexes, and even contributing to the increase of the occurrence of urban heat islands in several cities of the world. In this way, it becomes important that urban spaces allow greater thermal comfort to the inhabitants. There is a great scientific diversity of climatic studies, but there is a great difficulty in transmitting the knowledge related to microclimatic phenomena to urban planners and managers. The land use and occupation legislation that exists in most Brazilian cities provides general guidelines for the execution of building projects and urban interventions, however, those that specify adaptation measures to the impacts caused in the climate are rare. It is therefore perceived the need to analyze comfort in urban spaces and in what way the configuration of this space can contribute to its improvement. The main objective of this work is to determine the influence of urban configuration parameters on the thermal comfort of users. For that, the classification of four urban cuts according to the parameters of the ZCL system was performed, and the PET index relative to the level of thermal comfort of the users was evaluated. Thus, we sought to identify the thermal perception of users' satisfaction with the thermal environment, through structured interviews with pedestrians in the four selected ZCLs. The results point to the classification of four different types of ZCLs in the analyzed areas: ZCL 65, ZCL 3B, ZCL 2, ZCL 23. The PET index calculated at the hours of10h, 16h, and 19h ranged from 27 ° C (ZCL 65) to 48.6 ° C (3B). Both the PET and the perception of the users present thermal stress, with great perception of heat even in the period of 19h, where the areas were expected to have a cooling. In general, users reported higher satisfaction in ZCL 65, where the highest rates of tree vegetation were observed; even in situations of high air temperature. The correlation test showed that the level of comfort is lower as the impermeable and constructed areas are increased and the H / W ratio is increased. On the other hand, the comfort level increases when the permeable areas increase.
Urban configuration and thermal comfort at pedestrian level: studies in the city of São Carlos - SP
Keywords: Clima urbano; Conforto térmico urbano; Índice PET; Zonas Climáticas Locais; Urban climate; Urban thermal comfort; PET Index; Local Climate Zones; ENGENHARIAS::ENGENHARIA CIVIL; ENGENHARIAS